Regional carbonate compensation depth variability in the Pacific Ocean since the Oligocene - Dalvand, Faranak; Dutkiewicz, Adriana; Wright, Nicky M.; Mather, Ben R.; Müller, Dietmar (Frontiers in Earth Science, 2025)
Deep-sea carbonates constitute the primary deep carbon reservoir, playing a critical role in regulating the long-term global carbon cycle. Reconstructing the temporal evolution of carbonate flux to the seafloor requires estimating the changes in carbonate compensation depth (CCD), a key proxy, revealing the depth where the rate of calcium carbonate supply from biogenic ooze equals the rate of dissolution. However, regional CCD estimates across the Pacific, the deepest and largest ocean basin, remain poorly constrained, except for the eastern equatorial region. Here, we present six new regional reconstructions of the CCD across the Pacific Ocean, using a linear reduced major-axis regression of the carbonate accumulation rate (CAR) versus paleo-water depth, that include the effects of dynamic topography and eustasy. The CCDs show significant fluctuations of ∼1–1.2 km across the Pacific over the Neogene. Regional CCD models since the early Miocene suggest the influence of climate perturbations, Antarctic ice-sheet growth, and Pacific gateway reorganization on Pacific deep-water circulation and carbonate production. The western Pacific CCD shows a distinct deepening after ∼24 Ma, not seen in the eastern tropical Pacific, which we interpret as a delayed consequence of changes in deep water circulation in response to the expansion of the West Antarctic ice sheet into the marine realm at ∼26 Ma. Our models also reveal two significant late Miocene events, the carbonate crash and biogenic bloom, across both the western and eastern equatorial Pacific. However, a ∼1 Ma lag is noted for both events in the western tropical CCD, likely attributed to the successive effects of Panama Gateway constriction and shifts in the Western Pacific Warm Pool, respectively. The absence of the carbonate crash event from the western North Pacific reflects the regional nature of this event, predominantly influencing the Pacific equatorial region. Our analysis offers new insights into regional CCD variability across the Pacific Ocean and can be used to evaluate the evolution of deep-sea carbonate carbon reservoirs in the context of the long-term carbon cycle.